Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 1999
DOI: 10.1115/99-gt-099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stator Pressure Field on Upstream Rotor Performance

Abstract: Effects of stator pressure field on upstream rotor performance in a high pressure compressor stage have been assessed using three-dimensional steady and time-accurate Reynolds-averaged Navier-Stokes computations. Emphasis was placed on: (1) determining the dominant features of the flow arising from interaction of the rotor with the stator pressure field, and (2) quantifying the overall effects on time averaged loss, blockage, and pressure rise. The time averaged results showed a 20 to 40% increase in overall r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Sirakov explained this performance changes by a mechanism that the timeaveraged double leakage flow through the rotor tip clearance was reduced by the interaction between the rotor tip clearance flow and the pressure pulses, induced on the rotor blade pressure surface by the upstream stator wakes. Besides Graf [13], the periodic unsteadiness of the tip clearance flow was also observed by Mailach et al t151 who performed a detailed experimental investigation on the time-resolved behavior of the flow in the rotor tip region in a four-stage low-speed axial compressor. The experiment results showed that the unsteady periodic fluctuating tip clearance flow induced the propagation of rotating instabilities.…”
Section: Introduction Backgroundmentioning
confidence: 78%
“…Sirakov explained this performance changes by a mechanism that the timeaveraged double leakage flow through the rotor tip clearance was reduced by the interaction between the rotor tip clearance flow and the pressure pulses, induced on the rotor blade pressure surface by the upstream stator wakes. Besides Graf [13], the periodic unsteadiness of the tip clearance flow was also observed by Mailach et al t151 who performed a detailed experimental investigation on the time-resolved behavior of the flow in the rotor tip region in a four-stage low-speed axial compressor. The experiment results showed that the unsteady periodic fluctuating tip clearance flow induced the propagation of rotating instabilities.…”
Section: Introduction Backgroundmentioning
confidence: 78%
“…Graf [10] first discovered the periodic vibration of rotor tip flow field. Zhang [11] considered that the vibration of TLV was a dynamic balance between tip leakage flow and rotor tip loadings.…”
Section: Fluctuation and Forced Vibration Of Tip Leakage Vortexmentioning
confidence: 99%
“…Graf et al, through their numerical analyses, investigated the effects of the downstream stator on the upstream rotor [16]. They found that the tip vortex of the rotor blade has a periodic behavior.…”
Section: Introductionmentioning
confidence: 97%